Genomic plasticity and adaptive capacity of the quaternary alkyl-ammonium compound and copper tolerant Acinetobacter bohemicus strain QAC-21b isolated from pig manure - Pulami, Dipen; Schwabe, Lina; Blom, Jochen; Schwengers, Oliver; Wilharm, Gottfried; Kämpfer, Peter; Glaeser, Stefanie P.; Justus Liebig University Giessen (My University, 2023)
Here, we present the genomic characterization of an Acinetobacter bohemicus strain QAC-21b which was isolated in the presence of a quaternary alky-ammonium compound (QAAC) from manure of a conventional German pig farm. The genetic determinants for QAAC, heavy metal and antibiotic resistances are reported based of the whole genome shotgun sequence and physiological growth tests. A. bohemicus QAC-21b grew in a species typical manner well at environmental temperatures but not at 37 °C. The strain showed tolerance to QAACs and copper but was susceptible to antibiotics relevant for Acinetobacter treatments. The genome of QAC-21b contained several Acinetobacter typical QAAC and heavy metal transporting efflux pumps coding genes, but no key genes for acquired antimicrobial resistances. The high genomic content of transferable genetic elements indicates that this bacterium can be involved in the transmission of antimicrobial resistances, if it is released with manure as organic fertilizer on agricultural fields. The genetic content of the strain was compared to that of two other A. bohemicus strains, the type strain ANC 3994T, isolated from forest soil, and KCTC 42081, originally described as A. pakistanensis, a metal resistant strain isolated from a wastewater treatment pond. In contrast to the forest soil strain, both strains from anthropogenically impacted sources showed genetic features indicating their evolutionary adaptation to the anthropogenically impacted environments. Strain QAC-21b will be used as model strain to study the transmission of antimicrobial resistance to environmentally adapted Acinetobacter in agricultural environments receiving high content of pollutants with organic fertilizers from livestock husbandry.
Keywords: ddc:630